Effectiveness of Stage-of-Change–Based Health Education in Enhancing Community Capacity to Prevent Filariasis - Alpi Sri Rakhmayana; Susi Andriani; Nurlela Mufida (GLOBAL HEALTH SCIENCE GROUP, 2026)
Filariasis is a chronic infectious disease that can cause permanent disability and remains endemic in several regions of Indonesia, including Pidie District. Low public awareness and inadequate preventive practices hinder elimination efforts, underscoring the importance of effective health education. This study evaluate the effectiveness of health education based on the Stage-of-Change model in improving community capacity for filariasis prevention. A quasi-experimental pretest–posttest control group design was conducted with 100 respondents selected through purposive sampling. The intervention group (Delima Public Health Center area) received Stage-of-Change–based health education, while the control group (Padang Tiji Public Health Center area) received no specific intervention. Data on knowledge, attitudes, and preventive behaviors were collected using questionnaires with strong psychometric properties (Content Validity Index = 0.92; Cronbach’s Alpha = 0.87). Data were analyzed using univariate and bivariate techniques, with the Wilcoxon signed-rank test applied at α ≤ 0.05. Results showed significant progress in the intervention group, with participants advancing from precontemplation to preparation and action stages, accompanied by a marked increase in prevention capacity (p = 0.000, p < 0.05). In contrast, no significant change occurred in the control group (p = 0.342, p > 0.05). These findings confirm that SOC-based health education is more effective than conventional approaches and should be integrated into public health programs to strengthen community-based filariasis prevention.